A comparison of pedigree‐ and DNA‐based measures for identifying inbreeding depression in the critically endangered Attwater's Prairie‐chicken. Issue 21 (30th September 2013) - Hammerly, Susan C.; Morrow, Michael E.; Johnson, Jeff A.
Abstract The primary goal of captive breeding programmes for endangered species is to prevent extinction, a component of which includes the preservation of genetic diversity and avoidance of inbreeding. This is typically accomplished by minimizing mean kinship in the population, thereby maintaining equal representation of the genetic founders used to initiate the captive population. If errors in the pedigree do exist, such an approach becomes less effective for minimizing inbreeding depression. In this study, both pedigree‐ and DNA‐based methods were used to assess whether inbreeding depression existed in the captive population of the critically endangered Attwater's Prairie‐chicken (Tympanuchus cupido attwateri), a subspecies of prairie grouse that has experienced a significant decline in abundance and concurrent reduction in neutral genetic diversity. When examining the captive population for signs of inbreeding, variation in pedigree‐based inbreeding coefficients (fpedigree) was less than that obtained from DNA‐based methods (fDNA). Mortality of chicks and adults in captivity were also positively correlated with parental relatedness (rDNA) and fDNA, respectively, while no correlation was observed with pedigree‐based measures when controlling for additional variables such as age, breeding facility, gender and captive/release status. Further, individual homozygosity by loci (HL) and parental rDNA values were positively correlated with adult mortality in captivity and the occurrence of a lethal congenital defect in chicks, respectively, suggesting that inbreeding may be a contributing factor increasing the frequency of this condition among Attwater's Prairie‐chickens. This study highlights the importance of using DNA‐based methods to better inform management decisions when pedigrees are incomplete or errors may exist due to uncertainty in pairings.